Exploring the Impact of Sustainability, Corporate Social Responsibility, and Service Quality on Corporate Brand Reputation - Kok Ban Teoh; Hui Ling Lim; Fen Nee Cheah; Jia Xin Chai; Si Ling Chan; Wei Jie Chang; Wan Yung Cheah; A. J. Ali; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
This study aims to evaluate the effectiveness of PETRONAS’ sustainability practices, corporate social responsibility (CSR) initiatives, and customer service quality, as well as their combined impact on perceived brand reputation. In 2021, PETRONAS was ranked first in customer experience excellence in Malaysia by KPMG. This research employs a quantitative methodology, gathering data from 100 respondents via an online survey conducted through Google Forms. The findings from the survey reveal that PETRONAS’ dedication to sustainability, active CSR efforts, and high standards of customer service quality play a critical role in enhancing its brand reputation. Notably, sustainability practices, CSR initiatives, and customer service quality directly impact PETRONAS’ brand reputation. The study revealed that sustainability provided the strongest correlation with brand reputation. The study’s proposed framework can be applied to other businesses in the energy sector, encouraging the allocation of additional resources to sustainable energy services, improved environmental management, and advanced technology adoption to elevate customer service. This research provides valuable insights into how sustainability, CSR, and service quality contribute to maintaining brand reputation in the energy industry.